2015
DOI: 10.1007/s00405-015-3758-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two assessment methods for exercise-induced laryngeal obstructions

Abstract: Exercise-induced laryngeal obstructions (E-ILOs) are important differential diagnoses to exercise-induced asthma and are diagnosed by the continuous laryngoscopy exercise (CLE) test. There are two different methods for evaluating the severity of E-ILOs using recordings from the CLE test; the CLE score and EILOMEA. The aim of this study was to investigate the consistency between these methods. Using their respective method, the developers of each method evaluated 60 laryngoscopic recordings from patients with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…CLE testing has been successfully applied in numerous recent studies in this field of respiratory medicine 1 2 4–6 11 17 27–35. Studies addressing the validity and reliability of the CLE scoring system have reached somewhat variable conclusions 17 36 37. It nevertheless seems reasonable to conclude that experience is a factor that influences these issues.…”
Section: Discussionmentioning
confidence: 99%
“…CLE testing has been successfully applied in numerous recent studies in this field of respiratory medicine 1 2 4–6 11 17 27–35. Studies addressing the validity and reliability of the CLE scoring system have reached somewhat variable conclusions 17 36 37. It nevertheless seems reasonable to conclude that experience is a factor that influences these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have tried to validate a way to standardize the degree of obstruction by implementing the EILOMEA score, but we did not use this score because of its complex nature and the current lack of validation for its use for clinical purposes. The proposed scoring system of laryngeal obstruction by Matt et al seemed more useful.…”
Section: Discussionmentioning
confidence: 99%
“…Direct laryngoscopy, performed continuously during exercise, with the visual grade scoring system, is currently the gold standard and most widely utilised diagnostic methodology in the assessment of EILO [ 21 , 22 ]. In this study we provide the first evaluation of the validity of this approach and in fact found poor levels of agreement between expert raters using this approach, to semi-objectively quantify severity of EILO.…”
Section: Discussionmentioning
confidence: 99%
“…One system utilised a computer-generated scoring system based on mapping the glottic structures with a software system, EILOMEA [ 28 ]. Although reporting sensitivity and specificity of 1.00 for supraglottic EILO, a recent study by N orlander et al [ 22 ] found the method to be comparable to grade scoring, but impractical for clinical application. The software has yet to be validated in repeated measures and relies on a single snapshot still image for the measurements to then be applied.…”
Section: Discussionmentioning
confidence: 99%